Effect of phosphatic fertilizer compounds on aquatic primary production in saline water - Rajkumar K R (Department of Fishery Hydrography, College of Fisheries, 2005)
Fish production in farms largely depends on the primary productivity In the water bodies. Among many factors, plant nutrient levels and their availability in absorbable forms for the plankton is the most important one contributing to primary production. The plant nutrient element, phosphorus often found to limit the production, mainly due to the behavior of phosphorus compounds to remain in unavailable form in aquatic environment. Hence it becomes imperative to supplement phosphorus in suitable chemical form to achieve better production. While the dosage is also important, the salinity of water bodies has an interactive effect. Thus species of compounds in phosphatic fertilizer is vital. In the present study, two types of phosphatic fertilizers and combination of these fertilizers with additives were tested for their effect on aquatic primary production. Synthetic fertilizer namely single superphosphate and natural phosphatic fertilizer namely rock phosphate were selected for study. Commercial grade trisodium phosphate was used as additive in combination with single superphosphate and rockphosphate in 1: 1 ratio with respect to phosphate- P. All the above four fertilizer materials were tested in brackishwater having two salinity levels, a low salinity level of approximately 10 ppt and a high salinity level of approximately 20 ppt. Each fertilizer was added in three different doses, ie, O.lppm, 0.2 ppm and 0.4 ppm of phosphate-P. A set of control with two salinity level of water and without adding fertilizer were also run. All the experiments were done in duplicate, in accordance with statistically designed 2x4x4 Factorial Completely Randomized Design. The experiments were conducted in wide mouth polythene drums having 25 litre capacity using 20 liters of water. The experiment was set up in a protected, undisturbed, elevated place and kept exposed to sun light for 30 days. Volume loss due to evaporation was compensated by adding appropriate amount of water having corresponding salinity.